Preferences of institutional investors: Evidence from the Arab region - Elsayed, Mohamed Ahmed Magdy (AUC Knowledge Fountain, 2020)
In this research, we examine the preferences of institutional investors in the Arab region. Institutional investors’ investment decisions are based on various factors or measures that are used in assessing the worthiness of a company for investment. The research uses measures for stock risk and return, financial leverage, profitability, ownership concentration and trading activity, as well as measures for company size, value, sector, and country as predictor variables for the rate of institutional ownership and analyzes the impact of these variables. Using a cross-sectional model, the research gathers evidence from the Arab region’s leading stock markets by market capitalization for the year 2018/2019. For every stock market in the major Arab stock markets’ list, the constituents of its primary index are included as a basis for the data used in our research. We found that stock return, free-float ratio, return on assets, debt and company size, in terms of total assets and market capitalization to index ratio, have a significant and positive effect on institutional ownership. We also found that institutional ownership is higher in companies traded on Abu Dhabi, Dubai, and Casablanca stock markets, and that institutional investors favor the communications sector.